The path to a preferable future: Investing in System Innovation - Leadbeater, Charles; Smith, Shawn; Winhall, Jennie (The Rockwool Foundation, 2022)
Acknowledgements 3 1. Introduction 4 1.1. System Innovation 6 1.2. Sys tems Investing 7 2. News from the Frontier – An Emerging Field 10 2.1. Foundations 11 2.2. Private Capital 12 2.3. Government 12 2.4. Commun ity Capital 13 2.5. Movements 14 2.6. Framers 14 3. Systems Investment Strategy and Intent 15 3.1. Improvement or Transformation 16 3.2. Sol ving Problems or Opening Up Possibilities 18 3.3. Pragmatic Steps or T ransformational Intent 20 3.4. Four Keys to System Innovation 25 4. Un locking the Potential of Systems Investing 27 4.1. Orchestrate Opportu nities, Convene Capital 27 4.2. Create Attractive Systems Investment P ropositions 31 4.2.1. Get In Early 32 4.2.2. Build a Backbone 34 4.2.3 . Invest in Ecosystems, Not Single Interventions 34 4.2.4. Create Cond ucive Conditions for System Shifts 35 4.3. Create Accessible Investmen t Vehicles 36 4.4. Set Better Measures 40 4.5. Craft New Portfolios of Systems Change Interventions 42 5. Conclusions 43 Appendix 1. Learnin g Process and Contributors 47 Appendix 2. Systems Investing Portfolio Matrix 50